Fast adaptive interference cancellation in low cost SAW based chirp spread spectrum systems - Pohl, Alfred; Ostermayer, Gerald; Steindl, Reinhard; Reindl, Leonhard; Seifert, Franz; Weigel, Robert (IEEE Fifth International Symposium on Spread Spectrum Techniques and Applications, 1998)
For fast reliable data transmission in a heavily distorted indoor environment, a SAW based chirp spread spectrum system operating in the 2.45 GHz ISM is presented. Due to the implementation of SAW matched filters for impulse compression, the system design remains low cost. The use of a bandwidth as wide as allowed make it possible to overcome Rayleigh fading with large coherence bandwidths. A matched filter system is susceptible for jammers, passing the matched filter like a bandpass. Therefore a technique of fast adaptive cancellation without a loss of simplicity is presented. The system was tested in different electromagnetically polluted indoor areas. Some preliminary experimental results are presented.
elib2cris::1512001600,pohl1998b